A Decade of Avian Influenza in Bangladesh: Where Are We Now? - Nadia A. Rimi; Md. Zakiul Hassan; Sukanta Chowdhury; Mahmudur Rahman; Rebeca Sultana; Paritosh K. Biswas; Nitish C. Debnath; SK Shaheenur Islam; Allen G. Ross (Tropical Medicine and Infectious Disease, 2019)
Highly pathogenic avian influenza (HPAI) has been a public health threat in Bangladesh since the first reported outbreak in poultry in 2007. The country has undertaken numerous efforts to detect, track, and combat avian influenza viruses (AIVs). The predominant genotype of the H5N1 viruses is clade 2.3.2.1a. The persistent changing of clades of the circulating H5N1 strains suggests probable mutations that might have been occurring over time. Surveillance has provided evidence that the virus has persistently prevailed in all sectors and caused discontinuous infections. The presence of AIV in live bird markets has been detected persistently. Weak biosecurity in the poultry sector is linked with resource limitation, low risk perception, and short-term sporadic interventions. Controlling avian influenza necessitates a concerted multi-sector ‘One Health’ approach that includes the government and key stakeholders.